BUSINESS CULTURE AND THE GENOME OF BUSINESS EXCELLENCE IN CONSTRUCTION PRODUCTION - THE BASIS OF THE CULTURE OF INDUSTRIAL RELATIONS OF SOCIETY - Полосенко, Олександр; Хапанцев, Ігор; Савенко, Володимир; Нестеренко, Ірина; Клюєва, Вікторія (SWorldJournal, 2024)
The activity of each element of the organization: managers, executives - subjects and main actors of the organization carries teleonomy, i.e. expediency. In the target structure of organizations, for its survival, balance and stability, there is a need to